2012
DOI: 10.1016/j.eswa.2011.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Genetic programming for multibiometrics

Abstract: Biometric systems suffer from some drawbacks: a biometric system can provide in general good performances except with some individuals as its performance depends highly on the quality of the capture... One solution to solve some of these problems is to use multibiometrics where different biometric systems are combined together (multiple captures of the same biometric modality, multiple feature extraction algorithms, multiple biometric modalities. . . ). In this paper, we are interested in score level fusion fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We can note that the generated function all generate a monotonically decreasing ROC curve which allows to use our method. If the ROC curve does not present this shape, we would be unable to Figure 9: ROC Curve Of The Generated Multibiometrics Fusion Functions on the Validation Set of the BSSR1 dataset obtain the estimated EER (such drawbacks as been experimented using genetic programming [41] instead of genetic algorithms).…”
Section: Discussionmentioning
confidence: 99%
“…We can note that the generated function all generate a monotonically decreasing ROC curve which allows to use our method. If the ROC curve does not present this shape, we would be unable to Figure 9: ROC Curve Of The Generated Multibiometrics Fusion Functions on the Validation Set of the BSSR1 dataset obtain the estimated EER (such drawbacks as been experimented using genetic programming [41] instead of genetic algorithms).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the best weights is an intractable task due to the amount of comparisons needed. A genetic program [35] was developed to optimize these weights minimizing a fitness function in a finite number of steps, in this case 20 iterations. Intersession experiments under controlled conditions have been driven using the palm-side hand video subsets corresponding to each of the available light spectrum sectors, visible light and infrared light at 850 nm.…”
Section: Hand Geometrymentioning
confidence: 99%
“…Decision fusion algorithms can also be generated through machine learning. Giot and Rosenberger [2012] experimented with genetic programming [Koza 1992] to generate the fusion function, but results were only slightly better than weighted sums. found that combining 12-lead ECG signals at decision level performed better than fusion at the feature level.…”
Section: Feature Level Fusionmentioning
confidence: 99%